The Effect of High Selenite and Selenate Concentrations on Ferric Oxyhydroxides Transformation under Alkaline Conditions - Matulová, Michaela; Bujdoš, Marek; Miglierini, Marcel B; Cesnek, Martin; Duborská, Eva; Mosnáčková, Katarína; Vojtková, Hana; Kmječ, Tomáš; Dekan, Július; Matúš, Peter; Urík, Martin (International journal of molecular sciences, 2021)
Iron-based nanomaterials have high technological impacts on various pro-environmental applications, including wastewater treatment using the co-precipitation method. The purpose of this research was to identify the changes of iron nanomaterial's structure caused by the presence of selenium, a typical water contaminant, which might affect the removal when the iron co-precipitation method is used. Therefore, we have investigated the maturation of co-precipitated nanosized ferric oxyhydroxides under alkaline conditions and their thermal transformation into hematite in the presence of selenite and selenate with high concentrations. Since the association of selenium with precipitates surfaces has been proven to be weak, the mineralogy of the system was affected insignificantly, and the goethite was identified as an only ferric phase in all treatments. However, the morphology and the crystallinity of ferric oxyhydroxides was slightly altered. Selenium affected the structural order of precipitates, especially at the initial phase of co-precipitation. Still, the crystal integrity and homogeneity increased with time almost constantly, regardless of the treatment. The thermal transformation into well crystalized hematite was more pronounced in the presence of selenite, while selenate-treated and selenium-free samples indicated the presence of highly disordered fraction. This highlights that the aftermath of selenium release does not result in destabilization of ferric phases; however, since weak interactions of selenium are dominant at alkaline conditions with goethite's surfaces, it still poses a high risk for the environment. The findings of this study should be applicable in waters affected by mining and metallurgical operations.
Keywords: Selenic Acid; kyselina selenová; krystalizace; Selenious Acid; teplota; Iron Compounds; železo; Alkalies; železité sloučeniny; Chemical Precipitation; Spectroscopy, Fourier Transform Infrared; Minerals; spektroskopie Mossbauerova; Temperature; sloučeniny železa; spektroskopie infračervená s Fourierovou transformací; alkálie; chemická precipitace; Iron; minerály; Crystallization; kyselina seleničitá; Ferric Compounds; Spectroscopy, Mossbauer